Defense spending - economic growth nexus in selected OIC countries: a long-run causality analysis - Habibullah, Muzafar Shah; Mohd Tahir, Hirnissa; Abdul Hamid, Baharom (Penerbit Universiti Malaysia Terengganu, 2013)
This paper investigates the long run Granger causality between defense spending and economic growth for 20 selected Organization of Islamic Countries (OIC) by employing the Error-Correction Model (ECM) framework using annual data for the period 1960 to 2005. defense spending (milex) is measured using the ratio of defense spending to gross domestic product (GDP); while economic growth (rgdpc) is proxy by the real GDP per capita. The results of our study indicated that one way long run Granger causality was found running from economic growth to defense spending for Burkina Faso, Indonesia, Kuwait, Saudi Arabia, Sudan, Togo and Turkey. On the other hand, one way long run Granger causality was found running from defense spending to economic growth was found for Iran, Mauritania and Nigeria. However for the rest of the OIC countries, the results suggested no relationship between defense spending and economic growth.